Relationship Between Self-reported Apathy and Executive Dysfunction in Nondemented Patients With Parkinson Disease - Zgaljardic, Dennis J. (Cogn Behav Neurol, 2007)
OBJECTIVE: The prevalence of apathy was assessed across select cognitive and psychiatric variables in 32 nondemented patients with Parkinson disease (PD) and 29 demographically matched healthy control participants. BACKGROUND: Apathy is common in PD, although differentiating apathy from motor, cognitive, and/or other neuropsychiatric symptoms can be challenging. Previous studies have reported a positive relationship between apathy and cognitive impairment, particularly executive dysfunction. METHOD: Patients were categorized according to apathy symptom severity. Stringent criteria were used to exclude patients with dementia. RESULTS: Approximately 44% of patients endorsed significant levels of apathy. Those patients performed worse than patients with nonsignificant levels of apathy on select measures of verbal fluency and on a measure of verbal and nonverbal conceptualization. Further, they reported a greater number of symptoms related to depression and behavioral disturbance than did those patients with nonsignificant levels of apathy. Apathy was significantly related to self-report of depression and executive dysfunction. Performance on cognitive tasks assessing verbal fluency, working memory, and verbal abstraction and also on a self-report measure of executive dysfunction was shown to significantly predict increasing levels of apathy. CONCLUSIONS: Our findings suggest that apathy in nondemented patients with PD seems to be strongly associated with executive dysfunction.